ANALISIS SKALA EKONOMIS PADA INDUSTRI PERBANKAN SYARIAH DI INDONESIA - Suhel Suhel (Department of Development Economics, Universitas Sriwijaya, 2011)
This research also to analyze economies of scale . From this analysis, we will get the degree of Islamic Banking Industry,that is economies or diseconomies degree. The object of this research is Commonly Islamic Banking/ Bank Umum Syariah (BUS) that has operated at least since 2005. This research is using data panel during 2005- 2009 period. The data used is data of quarterly bank unit from financial report of Islamic Banking, there are contain the data of total financing, earnings, current assets, cost of employee, fixed assets and total deposits. From the calculation, has found that during 2005 – 2009 period, Islamic Banking Industry, from the calculation has found that economies of scale is more than 1 , it is mean that Islamic Banking Industry is in economies of scale condition. Individually, Islamic Banking also shows the same condition. The values shows that the existence of Islamic Banking Industryrelatively has a good performance. Keywords: Economic of Scale, Bank Syariah.